Mishaps during the monitoring of a congenital melanocytic nevus. - Bonifazi, E. (European Journal of Pediatric Dermatology, 2015)
Congenital melanocytic nevi may not be apparent at birth (3) or appear as a light brown stain; in the latter case often as in our case there are inside the stain lentigines or nevi that betray the melanocytic nature of the lesion and allow to differentiate it from hypermelanic nevus. Later on the differentiation is much easier because the hypermelanic nevus remains essentially unchanged, while melanocytic nevus can undergo significant changes, that are much more visible in more extensive congenital melanocytic nevi (1, 2). Today there is unanimous consensus in indicating the removal of a congenital melanocytic nevus not for the prevention of a malignant transformation, but for esthetic and psychosocial purposes: congenital nevi of the face are therefore most likely removed. A recurrent nevus frequently occurs after the removal of a congenital melanocytic nevus, due to the deep localization of its cells and should not alarm the doctor nor lead him to a radical removal, because there are in the literature cases of spontaneous regression of recurrent nevi (4).